2023
DOI: 10.1038/s41467-023-37527-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of peripheral blood from high-altitude pulmonary hypertension patients identifies a distinct monocyte phenotype

Abstract: Immune and inflammatory responses have an important function in the pathophysiology of pulmonary hypertension (PH). However, little is known about the immune landscape in peripheral circulation in patients with high-altitude pulmonary hypertension (HAPH). We apply single-cell transcriptomics to characterize the monocytes that are significantly enriched in the peripheral blood mononuclear cells (PBMC) of HAPH patients. We discover an increase in C1 (non-classical) and C2 (intermediate) monocytes in PBMCs and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, non-classical monocyte-derived macrophages have been shown to regulate vascular remodeling via chemokine secretion, classical complement activation, and TNF pathways ( 20 ). Non-classical monocytes and derived macrophages are increased in patients with altitude-induced PH and end-stage human pulmonary arterial hypertension (PAH) lung tissues ( 8 , 36 ). These characteristics are consistent with TLF + VCAM1 hi populations that emerge with prolonged hypoxia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, non-classical monocyte-derived macrophages have been shown to regulate vascular remodeling via chemokine secretion, classical complement activation, and TNF pathways ( 20 ). Non-classical monocytes and derived macrophages are increased in patients with altitude-induced PH and end-stage human pulmonary arterial hypertension (PAH) lung tissues ( 8 , 36 ). These characteristics are consistent with TLF + VCAM1 hi populations that emerge with prolonged hypoxia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller study compared the acute change at day 1 versus that at day 3, finding many of the genes were up-regulated at both timepoints [ 29 ], and there was also significant modulation of inflammatory pathways (at both timepoints) as we found here. There was also recently published single cell RNAseq of PMBCs from patients with chronic HA-induced PH, which identified an increase in monocyte density and interestingly a decrease in HIF1α at this late timepoint [ 30 ]. Markers of altered inflammation are similarly present in the peripheral blood of patients with idiopathic pulmonary arterial hypertension at the genetic and proteomic levels [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…By PBMC transcriptome analysis alone, we observed little interaction between DEX and HA exposures, with no clear revealing of mechanisms by which DEX protects against HA exposure by this approach. There is a possibility that DEX may help maintain cellular integrity as a functional impairment of peripheral immune cells in chronic HA-induced PH patients has been reported [ 30 ]. DEX also reduces lymphocyte activation, and decreases cytokine and chemokine production [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are other scenarios of vascular remodeling where monocytes and MDM display essential regulatory roles such as in pulmonary hypertension, thrombosis disorders, and venous malformation. Data obtained with single-cell analysis has revealed that non-classical and intermediate monocytes are enriched among all the monocyte subsets associated with pulmonary hypertension, and these phenotypes were associated with a decrease in hypoxia-inducible transcription factor-1a (HIF-1a) (180). Indeed, nonclassical (CD14 + CD16 + ) monocytes sense hypoxia, modulate pulmonary vascular remodeling, and induce pulmonary hypertension (181).…”
Section: Monocytes and Mdm In Other Vascular Alterationsmentioning
confidence: 99%